Gedichte zwischen lyrischer Poesie und diskursiver Prosa? Zum Beispiel Monika Rinck - Ralph Müller (Universität Trier, 2021)
This contribution examines the question of how contemporary lyric poetry expands upon established generic concepts by considering the work of Monika Rinck, one of the most striking voices among a generation of exceedingly talented poets who made their debut in the 2000s. In her poetry, we find numerous examples of how the expectations of lyric are deliberately undermined: among them, formal features reminiscent of prose, such as her tendency to use extremely long lines and prose-typical abbreviations, as well as her explicit interest in the discursive exploration of ‘concepts.’ As her essays suggest, this interest manifests itself most readily in Rinck’s efforts to avoid the totalizing economization of society (as well as art and language) and has, as a result, motivated the development of her own style within experimental language poetry. However, while Rinck has played a leading role in expanding the contemporary concept of poetry, the poetic principles to which she refers in her theoretical writings and poems are by no means new. In this article, her poem „Augenfühlerfisch“ (“eye-tentacle fish”) serves not only to illustrate her tendency to expand poetry into discursive prose but demonstrates how it is rooted in a long-standing philosophical tradition. The terminology used in the poem can be traced back to early modern epistemology and particularly to the foundation of scientific aesthetics by Alexander Gottlieb Baumgarten. In referring to Baumgarten’s definition of poetry as “fully sensuous speech [vollkommen sinnliche Rede]” (as well as the specific deployment of this definition by Johann Adolf Schlegel), it becomes clear that Rinck reactivates an epistemological potential in lyric that had been hidden by the paradigm of Erlebnislyrik [experiential lyric]. Moreover, Rinck is able to relax the Erlebnislyrik’s pretense to sincerity in part thanks to the same prose features, such as the multiplication of voices, already mentioned above.